Inadvertent left ventricular placement of ICD lead through the left subclavian artery right positioned in a patient with situs viscerum inversus and Kartagener syndrome. Issue 1 (January 2022) - Carretta, Domenico; Castellano, Maria; Gianfrancesco, Domenico; De Michele, Lucrezia; Cozzolino, Monica; Pedote, Pasquale; Angiletta, Domenico; Pulli, Raffaele; Colonna, Paolo; D'Agostino, Carlo
Abstract: Inadvertent placement of pacemaker and implantable cardioverter-defibrillator (ICD) leads in the left ventricle is a rare but well-recognized complication of device implantation. We report a case of an unicameral ICD lead inadvertently placed through the left subclavian artery right positioned, across the aortic valve into the left ventricle, in a patient with situs viscerum inversus. A transthoracic echocardiogram about a month after the procedure showed an unusual course of the lead. The lead was successfully removed without complications or sequelae. <Learning objective: Subclavian artery accidental puncture during pacemaker / implantable cardioverter-defibrillator implantation is an important complication. With grown up congenital heart this complication could occur more frequently and with more serious complications if the patient's anatomy is not well framed and deepened by specific instrumental examinations. If the above complication is managed quickly and competently and if the artery is not instrumented, it does not cause serious consequences.>